Note—A Note on Decision Making and Replacing Sure Prospects with Uncertain Prospects - Shubik, Martin (Management Science, 1973)
In the making of decisions where the valuation problem poses the major difficulty an individual may choose to replace a hard-to-evaluate certain prospect with a much easier to evaluate set of uncertain prospects.